Automatic Temperature Monitoring and Controlling Water Supply System - L. , Jaya Sekhar; P. , Shyamala Bharathi (International Journal of Psychosocial Rehabilitation, 2020)
Nothing is impossible with agriculture. 70% of the Indian population depends on agriculture. India ranks 74 out of 113 major countries in terms of the food security index. In India, agriculture is composed of many crops, with the foremost food staples being rice and wheat. Farmers can save their time by smart irrigation. This paper shows how the farmers can save their time using smart irrigation and how the pests that damage the crops can be killed on time. The crops are planted, and the moisture sensors are placed on the soil. If the moisture level of the soil is reduced, the sensors that have been placed in the soil have the ability to detect it, and automatically the crops are watered. In this paper, automatic irrigation is done by using sensors so that the crops will not be affected by dry conditions. The sensors placed on the field can detect the moisture level in the field, and according to it, the motor will be operated automatically. The information’s of the sensor data’s are sent through GSM. It collects data from different sensors deployed in a measured distance. It is powered by Arduino, a DC motor, and a GPRS module. It will check the water level, humidity, and moisture level of the crop. The sensor senses the water level and switches on the water pump automatically. All the commands are given by the Arduino and displayed on the LCD screen. It will also keep track of the previous data of humidity and temperature; hence, it is possible to set the required temperature based on the type of crop being cultivated.